Biogeography-Based Optimization: Algorithms and Applications - Zheng, Yujun; Lu, Xueqin; Zhang, Minxia; Chen, Shengyong (Springer Nature Singapore : Imprint: Springer, 2019)
XI, 221 p. 50 illus., 30 illus. in color.